Introduire l’éthique du care dans l’enquête de terrain - Coline Reille (Communication)
This paper tackles the question of how to integrate the ethics of care EoC into field research. It presents a method that is both reflexive and practical, drawing on insights from my own fieldwork. It demonstrates how EoC practices can be woven into research methodology, from choosing the presentation format to drawing up portraits of research participants. It emphasizes how incorporating EoC into field research provides a better understanding of certain research subjects, such as care work in animal professions, where certain characteristics have been defined. The paper shows that thinking about EoC as a research approach is not only achievable but also desirable. It illustrates a research approach that uses care as a research subject, epistemology, and research stance in the search for coherence between moral values, ethics, and scientific actions